The Compensation for Victims of Wrongful Shooting through Pretrial and Alternative Solutions in Indonesia - Shihaf Ismi Salman Najib; Geofani Lingga Meryadinata (JUSTISI, 2025)
This study aims to analyze the mechanism for filing and providing compensation for victims of wrongful shootings in pretrial according to criminal procedure law in Indonesia and explore alternative solutions for victims who do not get the proper compensation. The study method used is normative juridical, emphasizing a prescriptive nature because it solves society's legal problems. It is based on literature studies on primary legal materials such as laws, regulations, and court decisions and secondary legal materials such as journals and legal literature. The novelty of the study lies in the discussion of compensation mechanisms for victims of wrongful shootings and alternative solutions that have not been the primary focus in previous studies. This study explored the effectiveness of pretrial procedures as a solution for victims of wrongful shootings by law enforcement officers, as well as analyzed existing legal mechanisms to identify and propose improvements to prevent similar incidents in the future. The results show that victims of misfire can be compensated through the pretrial petition mechanism stipulated in KUHAP, Government Regulation No. 92/2015, and Ministry of Finance Decree No. 983/KMK.01/1983. However, the existing provisions still restrict the amount of compensation, which is often disproportionate to the victim's losses. Thus, alternative solutions that can be pursued include: (1) non-litigation settlement of cases through negotiation or mediation, (2) taking the criminal route by filing a lawsuit for deprivation of liberty and requesting compensation, and (3) filing a civil lawsuit based on unlawful acts (tort lawsuit). This study concludes that the government needs to revise Government Regulation No. 92/2015 by removing the minimum and maximum compensation limits. The amount of compensation should be determined by the District Court Judge, considering the level of loss suffered by the victim. Thus, justice for victims of wrongful shootings can be realized more optimally.